Subdural Empyema: How effective is The Burr Hole Drainage? (Medical Forum Monthly, 2024)
Background: Subdural empyema is a collection of pus between the dura mater and the arachnoid mater, usually unilateral and spreads rapidly through the subdural space until limited by specific boundaries (eg, falx cerebri, tentorium cerebelli, base of the brain, and foramen magnum). It is present in about 20% of all cases of intracranial abscesses.Aim and Objective: The aim was to identify the best mode of surgical treatment for SDEStudy Design: Experimental studyPlace and Duration of Study: This is a personal long term study of seventeen emergency patients of subdural Empyema admitted in Frontier Medical college/Women medical College Abbottabad and Private clinics at Abbottabad over seven years period from September 2006 to August 2013.Materials and Methods: All were operated soon after stabilization and proper investigations. There were 10 male and 7 female ratio(1.3:1). The majority of patients were between 10 and 20 years of age. The most common clinical presentation was headache, fever, neck stiffness, seizures or peri-orbital swelling; only seven patients had status epilepticus, While the erythrocyte sedimentation rate and white blood cell count were invariably elevated, the cerebrospinal fluid showed nonspecific pleocytosis in the patients who underwent lumbar puncture. The definitive per-operative diagnosis was made by contrast enchanced CT in all cases.Surgical treatment was by multiple burr holes in 8 patients, burr holes and small craniectomy in one, burr holes with catheter drainage in seven, and a large craniotomy in one.Results: The Success rate was 86% while 76% making an excellent recovery.Conclusion: These results compare favorably with those reported in other studies using craniotomy alone, and suggest that burr holes drainage is equally good a method treating subdural empyema.